Data from: Temporally dynamic habitat suitability predicts genetic relatedness among caribou - Yannic, Glenn; Pellissier, Loïc; Le Corre, Maël; Dussault, Christian; Bernatchez, Louis; Côté, Steeve D.; Pellissier, L.; Cote, S. D.; Le Corre, M.; Yannic, G. (Dryad, 2020)
Landscape heterogeneity plays a central role in shaping ecological and evolutionary processes. While species utilization of the landscape is usually viewed as constant within a year, the spatial distribution of individuals is likely to vary in time in relation to particular seasonal needs. Understanding temporal variation in landscape use and genetic connectivity has direct conservation implications. Here, we modelled the daily use of the landscape by caribou in Quebec and Labrador, Canada and tested its ability to explain the genetic relatedness among individuals. We assessed habitat selection using locations of collared individuals in migratory herds and static occurrences from sedentary groups. Connectivity models based on habitat use outperformed a baseline isolation-by-distance model in explaining genetic relatedness, suggesting that variations in landscape features such as snow, vegetation productivity and land use modulate connectivity among populations. Connectivity surfaces derived from habitat use were the best predictors of genetic relatedness. The relationship between connectivity surface and genetic relatedness varied in time and peaked during the rutting period. Landscape permeability in the period of mate searching is especially important to allow gene flow among populations. Our study highlights the importance of considering temporal variations in habitat selection for optimizing connectivity across heterogeneous landscape and counter habitat fragmentation. Yannic_data_DRYAD_RSPB-2014-0502Introductory information: Caribou (Rangifer tarandus) capture and genotype data. Please contact either Glenn Yannic (glenn-dot-yannic-at-gmail-dot-com) or Steeve D. Côté (Steeve-dot-Cote-at-bio-dot-ulaval-dot-ca) with any questions of location and genotype data. Identification – lab ID (ID number used in lab), capture ID (ID number used in field), sex (male or female). Capture Location - latitude (Y) and longitude (X) coordinates (datum = WGS84) of capture. Loci - names of microsatellite loci analyzed - 16 in ...